Texture analysis of pharynx in chronic phase Epstein-Barr virus infection - Baykara, Murat; Yaman, Okan (Bayrakol Medical Publisher, 2023)
Aim: Epstein-Barr virus (EBV) is a human herpes virus that can be found worldwide and causes latent infections. EBV is responsible for the etiology of infectious mononucleosis, Burkitt's lymphoma, and nasopharyngeal carcinoma (NPC) through the transformation of infected cells. In this study, it was aimed to investigate nasopharyngeal soft tissue differentiation by texture analysis in neck computed tomography (CT) images of EBV-positive individuals. Material and Methods: EBV-positive and negative healthy individuals of the same age and gender were selected consecutively from HIS and their neck CT images were evaluated with texture analysis. Results: While there was no significant difference between the groups in any of the same tissue parameters investigated for the largest lymph node in the neck, it was observed that only a small fraction of the 224 tissue parameters analyzed for each of the largest lymph node at the right neck IIA level, pharynx, and nasopharynx were statistically significant. Discussion: Despite some limitations, texture changes on CT in chronic EBV infection may lead to the identification of imaging markers that predict individuals at high risk of NPC.
Keywords: Human Herpesvirus 4; Epstein-Barr Virus Infections; Computerized Tomography; Computer-Assisted Image Processing; Nasopharyngeal Carcinoma